Traditional karyotyping vs copy number variation sequencing for detection of chromosomal abnormalities associated with spontaneous miscarriage. (October 2015) - Liu, S.; Song, L.; Cram, D. S.; Xiong, L.; Wang, K.; Wu, R.; Liu, J.; Deng, K.; Jia, B.; Zhong, M.; Yang, F.
ABSTRACT Objectives To compare the performance of traditional G‐banding karyotyping with that of copy number variation sequencing (CNV‐Seq) for detection of chromosomal abnormalities associated with miscarriage. Methods Products of conception (POC) were collected from spontaneous miscarriages. Chromosomal abnormalities were detected using high‐resolution G‐banding karyotyping and CNV sequencing. Quantitative fluorescent polymerase chain reaction analysis of maternal and POC DNA for short tandem repeat (STR) markers was used to both monitor maternal cell contamination and confirm the chromosomal status and sex of the miscarriage tissue. Results A total of 64 samples of POC, comprising 16 with an abnormal and 48 with a normal karyotype, were selected and coded for analysis by CNV‐Seq. CNV‐Seq results were concordant for 14 (87.5%) of the 16 gross chromosomal abnormalities identified by karyotyping, including 11 autosomal trisomies and three sex chromosomal aneuploidies (45, X). Of the two discordant results, a 69, XXX polyploidy was missed by CNV‐Seq, although supporting STR marker analysis confirmed the triploidy. In contrast, CNV‐Seq identified a sample with 45, X karyotype as a 45, X/46, XY mosaic. In the remaining 48 samples of POC with a normal karyotype, CNV‐Seq detected a 2.58‐Mb 22q deletion associated with DiGeorge syndrome and nine different smaller CNVs of no apparent clinical significance. Conclusions CNV‐Seq used in parallel with STR profiling is a reliable and accurate alternative to karyotyping for identifying chromosome copy number abnormalities associated with spontaneous miscarriage. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.